Malay Traditional Institution and The Traditional Dress Policy in Public Spaces - Mhd. Rafi; Sujianto; Albintani, Muchid; Asriwandari, Hesty (Moestopo International Review on Social, Humanities, and Sciences, 2026)
This article aims to analyze the dynamics of the implementation of the Malay fashion preservation policy as a strategy for maintaining cultural identity in Riau Province, as well as to evaluate the strategic role of the Riau Malay Traditional Institution (LAM Riau) in regional cultural governance. This research method uses a qualitative approach with a descriptive design. Data collection was conducted through a documentation study of various cultural policies in Riau Province and in-depth interviews with key informants determined through a purposive sampling technique with 11 respondents with the criteria of inherent authority, cultural actors and key stakeholders in cultural policy in Riau Province. The results of the study indicate that the implementation of the traditional fashion policy has been dominantly internalized in the government bureaucratic system, but its manifestation in the public sphere is still symbolic-administrative and has experienced a reduction in philosophical meaning. LAM Riau plays a central role as a government partner and guardian of values ​​to ensure that modernization does not erode traditional norms. The main challenges faced include the distortion of the younger generation's understanding of dress ethics and the hegemony of popular culture.